A snapshot of yield management practices among front office employees in Kuala Lumpur five star hotels / Dian Aszyanti Atirah Mohd Asri - Mohd Asri, Dian Aszyanti Atirah (2014)
The purpose of this study was to propose the Yield Management practices consist of upselling, upgrading and overbooking practices among the front office employees and to test the relationship between YM and hotel performance. Additionally, this study also intended to identify the effect of employee reward scheme between YM and hotel performance and identified the most agreeable YM challenges faced by the front office employees. This study was specifically developed among the front office employees including receptionist and reservationist in Kuala Lumpur five-star hotels. Thus, convenience sampling was chosen and 240 questionnaires have been distributed to all 24 five-star hotels. It was specifically developed for full service, upscale hotels. Descriptive analysis has been computed on YM practices where upselling practice was chosen to be the most agreeable practices followed by upgrading and overbooking. In line with that, the relationship of YM practices and hotel performance was positively significant related (p < 0.05). Surprisingly, employee rewards scheme does not moderate the relationship between YM and hotel performance which contradict to the previous literature. Therefore, having insufficient knowledge on YM practices had given the most agreeable challenges among the front office employees. The findings of this study provided hoteliers with a better knowledge on YM practices from the employees’ perspectives. The top management also could get better in-sights on how to improve their current YM practices to augment hotel performance. Findings indicate that rewards scheme does not moderated the relationship between YM and hotel performance. Finally, this study also added to the existing literature of YM that was dominantly focused on the management perspectives.